2004
DOI: 10.1038/sj.bjc.6601489
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 selective inhibition with NS-398 suppresses proliferation and invasiveness and delays liver metastasis in colorectal cancer

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) have been reported to reduce the risk and mortality of colorectal cancer (CRC) by inhibiting the activity of cyclooxygenase (COX). The present studies were directed to determine whether selective COX-2 inhibition reduces CRC tumour cell proliferation and invasion/migration, and the possible cellular and molecular mechanisms involved. The MC-26 cells are a highly invasive mouse CRC cell line expressing COX-2 protein. NS-398 (100 mM), a highly selective COX-2 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 56 publications
(62 reference statements)
5
74
1
Order By: Relevance
“…Another relevant outcome of this study was the documentation of the expression of COX-2, c-KIT and HER-2/neu in uterine carcinosarcomas, because we know that these same gene products are molecular targets for innovative treatments, such as COX-2 inhibitors, STI571 and trastuzumab, which had been already proven beneficial in colorectal cancer, GIST and breast carcinoma, respectively [16,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant outcome of this study was the documentation of the expression of COX-2, c-KIT and HER-2/neu in uterine carcinosarcomas, because we know that these same gene products are molecular targets for innovative treatments, such as COX-2 inhibitors, STI571 and trastuzumab, which had been already proven beneficial in colorectal cancer, GIST and breast carcinoma, respectively [16,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…These effects of tumor COX-2-dependent factors on tumor-activated LSECs are consistent with reported antimetastatic effects of COX-2 inhibitors in the liver. 38 Finally, C26 cell-derived factors impaired LSL-stimulating effects of LSECs leading to anti-tumor cytotoxicity inhibition and IFN-gamma/IL-10 secretion ratio decrease. Nonetheless, ManR deficiency in ManR À/À mice and blockade of ManR on tumor-stimulated LSECs-either directly with specific neutralizing antibodies or indirectly by inhibition of ManR-stimulating factor production through IL-1 and COX-2 inhibitors-restored antitumor cytotoxicity of LSLs interacting with tumor-activated LSECs.…”
Section: Discussionmentioning
confidence: 99%
“…This can reduce tumor cell proliferation and invasion. It has also been shown that COX-2 inhibitor significantly reduced tumor-induced MMP-2 and MMP-9 expression in cancer models (21,46). To elucidate the possible link between COX-2/VEGFR and the proteolytic enzymes, cells were treated with SC-236 or CBO-P11 to examine the effects on MMP-2 and MMP-9 as well as uPA and uPAR on gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are involved in ECM degradation (17) and the activity is associated with invasiveness and metastasis in tumor cells (18). MMP-2 and MMP-9 are the two major enzymes that can selectively degrade type IV collagen and facilitate tumor invasion and metastasis in various experimental models, including gastric, colon, and breast cancers (19)(20)(21). Administration of nicotine increased the severity of choroidal neovascularization and also reversed the VEGF-induced suppression of MMP-2 activity in mice (22), showing that MMP could play a role in the angiogenesis induced by nicotine.…”
Section: Introductionmentioning
confidence: 99%